Monoclonal Antibody Therapies for HPV-Associated Cervical Cancer: A Literature Review - Dariatul Janah; Andi Yasmon (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Cervical cancer is a malignancy in gynecology attributable to human papillomavirus (HPV) infection with high prevalence and mortality caused by persistent infections of hr-HPV 16 and 18. HPV with various virulence factors can evade the immune system and integrate its genetic material into the host cell DNA. HPV replication only occurs in differentiated cells in the upper layer of the mucosal epithelium or skin developing into cancer. Globally, approximately 70% of patients diagnosed with cervical cancer present at an advanced or late stage causing therapy to be ineffective. The use of HPV-specific monoclonal antibodies for therapy with cervical cancer, as an alternative or complement will give new insight into managing the patients. The development of monoclonal antibodies having potential as an alternative therapy began to be used as a therapy in the advanced, recurrent, persistent or metastatic cervical cancer. This review specifically discusses monoclonal antibodies that have been approved by FDA for therapy against cervical cancer. In clinical trials, adding bevacizumab to combination chemotherapy extended median overall survival by 3.7 months in patients with recurrent, persistent, or metastatic cervical cancer. Pembrolizumab significantly prolonged progression-free and overall survival compared to placebo when combine to chemotherapy (with or without bevacizumab) in similar patient populations. Likewise, tisotumab-vedotin demonstrated greater over chemotherapy as second-line or third-line therapy for recurrent cervical cancer. Therefore, this article review aims to describe the types and roles of monoclonal antibodies that have potential to be used as a single or combination therapy especially chemotherapy for patients with cervical cancer.